Pemahaman Dan Praktik Sakramen Tobat Di Kalangan Mahasiswa Katolik Jurusan Administrasi Negara Fakultas Ilmu Sosial Dan Politik Universitas Nusa Cendana Kupang: Analisis Dan Refleksi Teologis-Pastoral - Gabriel A.I Benu; Siprianus Soleman Senda; Yohanes Darisalib Jeramu; Maria D.C. Benu (BULLET : Jurnal Multidisiplin Ilmu, 2023)
One of the sacraments in the Catholic Church is the sacrament of penance. Through this sacrament a sinful Catholic believer declares repentance by confessing his sins and receiving forgiveness from God through the serving priest. Catholic students as Catholic believers live their faith, among others, by celebrating the sacrament of repentance. However, in reality, there is a phenomenon which shows that the sacrament of repentance is not well understood by Catholic students. This research was conducted on Catholic students of the Department of State Administration, Faculty of Social and Political Sciences, University of Nusa Cendana, Kupang. The results show that there are still many Catholic students who do not understand the meaning of this sacrament and have an impact on the practice of celebrating it. For this reason, catechism efforts are needed for students to have a correct understanding of the sacrament of repentance and to celebrate it regularly with full awareness of faith.